Geological Perspective for Geotourism Development in Uthai Thani Province, Thailand - SINGTUEN, Vimoltip; WON-IN, Krit (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.9.5(29).12, 2018)
Uthai Thani is a fascinating city in central Thailand and has the uniqueness of geodiversity, nature, culture, and history, which makes it ideal for geotourism development. The lifestyle of the local population is linked to nature and the river, making the area very interesting for tourist. It also has a fantastic mountainous region in the western part including karst topography, granite batholith, and numerous small hills. The study area consists of seven geosites, which are Sakae Krang River, Kao Pla Ra Mountain, Hup Pa Tat Cave, Samor Thong Hot Spring, Khuan Khun Kaew Reservoir, Saiber Waterfall, and Huai Kha Khaeng Wildlife Sanctuary. The Kao Pla Ra mountain is the highlight of this region, which has many prehistoric cliff-paintings. This geotourism announcement can educate the tourists to understand the geologic processes and has many advantages for the local and national sustainable development in the travel industry, economy, geology, history, and society.